Key success factors and information availability in cultural heritage tourism attractions - Hughes, Michael; Carlsen, Jack; Peel, V.; Pocock, C.; Frost, W. (University of Technology Sydney, 2007)
Operating a successful cultural heritage tourism (CHT) business requires both knowledge of the heritage conservation needs and sound business practice. Using a combination of qualitative and quantitative methods, this study sought to compare the success factors identified by practitioners with the research effort apparent in the CHT literature. A list of nine key success factors was devised based on existing literature and CHT practitioner interviews. Success factors included: clear objectives and concepts, financial planning; Marketing and market research; understanding visitor flows and location; effective human resource management; understanding differentiation and tourism life cycle; addressing quality and authenticity; having expertise in conservation and promotion; and effective Interpretation The success factors were used to guide a quantitative thematic analysis of 284 publications relating to CHT. Numbers of documents addressing the nine respective success factors was ascertained. Analysis found the bulk of the literature focused on two of the nine success factors, mainly: concepts, objectives; and quality and authenticity. Although five success factors were business practice focussed, only a small proportion of the literature represented these. The analysis identified a disconnect between the research effort in CHT and the knowledge and skills needs of practitioners.